Attention to the macroeconomy - Sebastian Link; Andreas Peichl; Christopher Roth; Johannes Wohlfart (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We provide evidence on the dynamics, drivers, and consequences of attention to the macroeconomy using tailored panel surveys of German firms and households. Draw-ing on novel measures of attention based on open-ended questions collected before and during a historic shock to inflation, we document three sets of results: First, at-tention to the macroeconomy is characterized by large and persistent individual het-erogeneity, responds strongly to changes in the economic environment, and is nega-tively correlated with attention to household- or firm-level topics. Second, more at-tentive respondents are more likely to adjust inflation expectations during the shock, have higher confidence in their beliefs, and hold smaller misperceptions about re-alized inflation, yet their expectations about future inflation deviate more strongly from professional forecasts. Third, personal experiences are associated with house-holds' attention allocation and belief formation during the shock in a time-varying way, consistent with similarity-based recall. Our results have implications for model-ing attention allocation and expectation formation about the economy.
Keywords: D83; D84; E71; 330; Attention; expectation formation; personal experiences; inflation